Agricultural water storage in developing countries - McCartney, Matthew P.; Smakhtin, Vladimir U. (2011)
This paper addresses the need for agricultural water storage in developing countries. Rainfall variability is an important factor in development and translates directly into a need for water storage. In many places rainfall variability is likely to be amplified (even where the total amount of rain increases) as a result of climate change. If planned and managed correctly, various forms of water storage can increase water security and agricultural productivity thereby contributing to improved livelihoods and reduced rural poverty. However, ill-conceived water storage is a waste of financial resources and, rather than mitigate, may aggravate negative climate change impacts. Systems that combine complementary storage options are likely to be more adaptable and acceptable than those based on a single storage type. More systematic planning and management is required to avoid the mistakes of the past and to ensure more effective and suitable storage systems for the future.